Global engineering ethics - Luegenbiehl, Heinz C.; Clancy, Rockwell F. (Butterworth-Heinemann is an imprint of Elsevier, 2017)
Global Engineering Ethics introduces the fundamentals of ethics in a context specific to engineering without privileging any one national or cultural conception of ethics. Numerous case studies from around the world help the reader to see clearly the relevance of design, safety, and professionalism to engineers. Engineering increasingly takes place in global contexts, with industrial and research teams operating across national and cultural borders. This adds a layer of complexity to already challenging ethical issues. This book is essential reading for anyone wanting to understand or communicate the ethics of engineering, including students, academics, and researchers, and is indispensable for those involved in international and cross-cultural environments.